KETERBATASAN RESPON HEMOGLOBIN DAN SENG SERUM TERHADAP SUPLEMENTASI SENG (IN) DAN BESI (FE) PADA ANAK USIA 6-24 BULAN - Hadi Riyadi; Sudjana Sibarani; Rimbawan Rimbawan; Muhilal Muhilal (Media Gizi dan Keluarga, 2004)
ABSTRACT. The objective of  this study  was to investigate the efficacy of  iron and zinc supplementation on anemic status and zinc status of children aged 6-24 months. The study was a double-blind, randomized, placebo-controlled trial in which 173 children aged 6-24 months were randomly assigned to receive 15 mg Fe+ 15 mg Zn daily 30 mg Fe+30 mg Zn weekly or placebo for 5 months. As expected, no significant difference in the baseline hemoglobin and serum zinc concentration and nutrient intake between the three supplementation groups. In the children aged 6-24 months, micronutrient deficiencies were prevalent. Almost 50% of the children were anemic, and 20% of them were zinc deficient. The anemic children had a 2.5-fold greater risk of  zinc deficient than did the non-anemic children. This could indicate the existence of concurrent nutritional deficiencies. At the end of the 5mo supplementation period, the daily and weekly Fe+Zn supplementation tend to increased hemoglobin concentrations, but there were no significant difference compared with the placebo. The daily and weekly Fe+Zn supplementation did not significantly affect serum zinc concentration compared with the placebo.   Keyword: suplementasi, anemia, besi dan seng.